Penciptaan Video Seni Instalasi "Narkoba Berbahaya" - Febri, I Wayan Nain (PERSPEKTIF, 2020)
This article discusses creating drugs that discuss new types of drugs that are very dangerous, so presenting images of drug victims in this video because it can be a concern that will increase the danger for adolescents in the productive period. Problems with the use of drugs. To discuss this problem, reference theory from (Sp, 2004) and (Murti, 2009) is used. The stages of the announcement process of the installation video of "Dangerous Drugs", discussed the stages of the creation of a television program including pre-production, production, and post-production. The results of the discussion of this article are the work of creating responses to phenomena that occur around social life. This study explains that the presence of a senior video on the installation of 'Dangerous Drugs' can trigger the creation of an anti-narcotics campaign with a form of senior video installation that is easily understood by many people who help everyone can help people who care about drugs, and always be vigilant in the social environment . This video also shows the big problem that is surrounding the future of the young generation in Indonesia.